Serious Games in Secondary Education to Introduce Circular Economy: Experiences With the Game EcoCEO - Roba, Julie; Kuppens, Tom; Janssens, Lise; Smeets, Anse; Manshoven, Saskia; Struyven, Katrien (Frontiers in Sustainability, 2021)
The concept of the circular economy is being proposed as an alternative for the current linear economy. However, little research has been done on how to integrate this topic within education. Serious games are suggested as an appropriate way to create awareness about and stimulate behavioral change towards sustainable development. Therefore, the serious game ecoCEO has been developed to introduce the circular economy concept within upper secondary education. The game’s intention is to introduce students to the challenge of resource scarcity, circular product design, sustainable entrepreneurship and circular business models. EcoCEO has been tested among 42 students, whose written reflections were qualitatively examined. EcoCEO appears successful, at least partially, in contrasting the circular economy with the linear economy and in conveying relevant concepts such as recycling and reuse. EcoCEO also illustrates the importance of the circular economy within the context of material scarcity. Moreover, most students seem to have a good impression of the role and responsibilities of a (sustainable) entrepreneur. Despite its difficulty level, the majority of the students reported having fun while playing ecoCEO.